2002
DOI: 10.1097/00005537-200206000-00010
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Report on Micronized AlloDerm Injection Laryngoplasty

Abstract: Micronized AlloDerm appears to be a safe new material that is suitable for injection laryngoplasty. Long-term results are pending.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 20 publications
2
71
1
1
Order By: Relevance
“…Other studies showed agreeing results concerning VHI improvement and voice acoustic patterns, as in patients submitted to laryngoplasty to treat unilateral vocal fold paralysis. The statistically significant improvement on voice acoustic patterns associated with VHI improvement showed that in some pathological cases there is agreement between the VHI and the vocal analysis objective patterns [25][26][27]35,38 . Despite the extensive publication on voice and speech alterations associated with hearing loss of such characteristics, there is no report on the use of VHI to assess these complaints from patients with hearing loss.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Other studies showed agreeing results concerning VHI improvement and voice acoustic patterns, as in patients submitted to laryngoplasty to treat unilateral vocal fold paralysis. The statistically significant improvement on voice acoustic patterns associated with VHI improvement showed that in some pathological cases there is agreement between the VHI and the vocal analysis objective patterns [25][26][27]35,38 . Despite the extensive publication on voice and speech alterations associated with hearing loss of such characteristics, there is no report on the use of VHI to assess these complaints from patients with hearing loss.…”
Section: Introductionmentioning
confidence: 83%
“…VHI was used as a means to measure the voicerelated handicap in different disease groups, such as organic dysphonias 15 , presbyphonia 16 , professional use of one's voice 17,18 , gastroesophageal reflux disorder (GERD) and laryngopharyngeal reflux disorders 19,20,21 , adduction and abduction spasmodic dysphonia 22,23,24 , thyroplasties 25,26,27 , microsurgery for benign 28,29 and malignant 30,31,32 disorders, radiography for laryngeal cancer 33 , use of tracheoesophageal 34 and speech therapy 35,36 . Numerous authors compared other methods of vocal assessment.…”
Section: Introductionmentioning
confidence: 99%
“…1 Since the procedure was first described in 1911 by Brunings, there has been continuous evolution both in terms of injection materials and injection routes. 1,2 Broadly speaking, injectable fillers can be temporary, for example, gelfoam, fat, collagen, acellular dermis, and hyaluronic acid (HA), [3][4][5][6][7] or permanent or semipermanent, for example, teflon, and more recently hydroxylapatite and silicone. [8][9][10] There are advantages and disadvantages to each material and none can be considered ''ideal'' in every situation.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies with other [[parms resize(1),-pos(50,50),size(200,200),bgcol(156)]] demonstrated improved phonatory results lasting longer than expected based on the material's characteristics. 7,13,14 This, most likely, is not because of the retention of the material, but rather owing to partial reinnervation with or an undescribed phenomenon of central retraining that occurs when the body is given the tools to make improvements (voice therapy and a temporary injection) and then remember them.…”
Section: Discussionmentioning
confidence: 99%